New Insights into the PPARγ Agonists for the Treatment of Diabetic Nephropathy - Zhanjun Jia; Ying Sun; Guangrui Yang; Aihua Zhang; Songming Huang; Kristina Marie Heiney; Yue Zhang (PPAR Research)
Diabetic nephropathy (DN) is a severe complication of diabetes and serves as the leading cause of chronic renal failure. In the past decades, angiotensin-converting enzyme inhibitors (ACEIs)/angiotensin II receptor blockers (ARBs) based first-line therapy can slow but cannot stop the progression of DN, which urgently requests the innovation of therapeutic strategies. Thiazolidinediones (TZDs), the synthetic exogenous ligands of nuclear receptor peroxisome proliferator-activated receptor-γ (PPARγ), had been thought to be a promising candidate for strengthening the therapy of DN. However, the severe adverse effects including fluid retention, cardiovascular complications, and bone loss greatly limited their use in clinic. Recently, numerous novel PPARγ agonists involving the endogenous PPARγ ligands and selective PPARγ modulators (SPPARMs) are emerging as the promising candidates of the next generation of antidiabetic drugs instead of TZDs. Due to the higher selectivity of these novel PPARγ agonists on the regulation of the antidiabetes-associated genes than that of the side effect-associated genes, they present fewer adverse effects than TZDs. The present review was undertaken to address the advancements and the therapeutic potential of these newly developed PPARγ agonists in dealing with diabetic kidney disease. At the same time, the new insights into the therapeutic strategies of DN based on the PPARγ agonists were fully addressed.